THE EFFECT OF CLUSTERING TECHNIQUE COMBINED WITH PEER ASSESSMENT UPON STUDENTS’ WRITING COMPETENCY OF THE EIGHTH GRADE STUDENTS ON SMP NEGERI 3 SINGARAJA IN THE ACADEMIC YEAR 2015/2016 - ., Ni Putu Eka Novitri; ., Prof. Dr. Anak Agung Istri Ngr. Marha; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengetahui ada atau tidaknya perbedaan yang berarti antara siswa yang diajarkan dengn menggunakan Teknik Clustering dikombinasikan dengan Peer Assessment dan siswa yang diajarkan dengan menggunakana teknik menulis yang konvensional. Rancangan penelitian ini adalah Post-test Only Control Group Design. Populasi penelitian ini adalah siswa kelas delapan di SMP Negeri 3 Singaraja. Sampel penelitian ini berjumlah 68 siswa yang dipilih dengan menggunakan teknik random sampling. Hasil analisis memperlihatkan bahwa ada perbedaan yang berarti dalam kemampuan menulis antara siswa yang diajarakan dengan menggunakan teknik clustering dikombinasikan dengan peer assessment dan siswa yang diajarkan dengan menggunakan teknik menulis konvensional (tobs = -7.322, Sig. 0.001) diaman siswa yang diajarkan dengan menggunakan teknik clustering dikombinasikan dengan peer assessment memiliki kemampuan menulis yang lebih baik.Kata Kunci : Kemampuan menulis, Teknik Clustering dan Peer Assessment This study was aimed at investigating whether there was a significant difference in writing competency of students who were taught by using Clustering Technique combined with Peer Assessment and those who were taught by using Conventional Writing Technique. The research design of this study was Posttest Only Control Group Design. The population of this study was the eighth grade students of SMP Negeri 3 Singaraja. The sample of this study was 68 students which were selected by using random sampling technique. Result of analysis show that there is a difference in writing competency between students taught by using Clustering Technique combined with Peer Assessment and those taught by using conventional writing technique, (tobs = -7.322, Sig. 0.001) in which the students taught by using Clustering Technique combined with Peer Assessment achieve better in writing achievement.keyword : Writing Competency, Clustering Technique, and Peer Assessment